2021
DOI: 10.1007/s00402-021-04299-9
|View full text |Cite
|
Sign up to set email alerts
|

Three-stage limb salvage in tibial fracture related infection with composite bone and soft-tissue defect

Abstract: Introduction Managing critical-sized tibial defects is one of the most complex challenges orthopedic surgeons face. This is even more problematic in the presence of infection and soft-tissue loss. The purpose of this study is to describe a comprehensive three-stage surgical protocol for the reconstruction of infected tibial injuries with combined bone defects and soft-tissue loss, and report the clinical outcomes. Materials and methods A retrospective stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 37 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…The only available data pertaining to tibial NUs were used in the pooled analysis [ 39 ]. The remaining articles included single-intervention cohorts of either the Ilizarov method ( n = 22) [ 30 38 , 40 , 42 51 , 53 , 56 ] or the Mq technique ( n = 8) [ 17 20 , 41 , 52 , 55 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The only available data pertaining to tibial NUs were used in the pooled analysis [ 39 ]. The remaining articles included single-intervention cohorts of either the Ilizarov method ( n = 22) [ 30 38 , 40 , 42 51 , 53 , 56 ] or the Mq technique ( n = 8) [ 17 20 , 41 , 52 , 55 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…crest: 12 ± Allog 31 Ozpolat [ 55 ] 24.6 (13–40) 2.8 (1–6) Free flaps: 3, Local flaps: 4 2–4 wks IV, + 2 wks PO nr Il. crest: 11 Allog: 10 32 Corona [ 56 ] 48 (15–110) 3.4 (0–15) Free flap: 21, Local flap: 10, VAC: 28 IV: 10d, Oral: 4–6 wks 17.8 (9–32) 11 AB antibiotic; AS acute shortening, Allog. supplementary allograft, BG bone graft, BMP bone morphogenetic protein, Br-sp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first report describing an orthoplastic approach combining MIMT and PRECICE nail in the management of septic non-union of tibial pilon fractures. Other proposals have combined the orthoplastic approach with definitive bone reconstruction using principles of distraction osteogenesis with external fixation, such as Corona et al, who reported 31 patients with a limb salvage rate of 93.5 % (29/31) and return to work rate of 83 % [8] . Similarly, Bauer et al, in a cohort of 50 patients reported that in 95 % of the cases the limb was not amputated [9] .…”
Section: Discussionmentioning
confidence: 99%
“…In practice, such patients have a strong demand for limb salvage treatment. The treatment principle is staged surgeries, including controlling infection, soft tissue and bone reconstruction, and limb function recovery 4 . Although the treatment principle is clear, the treatment course is long.…”
Section: Introductionmentioning
confidence: 99%